Examining the Effect of Profitability, Corporate Governance, Firm Size, and Capital Structure on Firm Value: The Moderating Role of CSR - Manik, Defriyanti Cicilia; Sihombing, Pardomuan (International Journal of Entrepreneurship and Business Management, 2025)
This study analyzes the influence of determinants on company value with CSR as a moderator in Construction Companies Listed on the Indonesia Stock Exchange from 2018 to 2023. The sampling technique used in this study is purposive sampling. The sample in this study consists of 6 companies. This study uses panel data analysis with MRA in E-views 12. The results of the analysis indicate that ROE and KM do not influence company value. Firm size has a negative influence, while DER has a positive influence on company value. CSR does not have a significant influence on company value and is unable to moderate the relationship between independent variables and company value.